DPP (Dipeptidyl Peptidase)-4 Inhibition Potentiates the Vasoconstrictor Response to NPY (Neuropeptide Y) in Humans During Renin-Angiotensin-Aldosterone System Inhibition. Issue 3 (September 2018) - Hubers, Scott A.; Wilson, Jessica R.; Yu, Chang; Nian, Hui; Grouzmann, Eric; Eugster, Philippe; Shibao, Cyndya A.; Billings, Frederic T.; Jafarian Kerman, Scott; Brown, Nancy J.
Abstract : DPP (dipeptidyl peptidase)-4 inhibitors are antidiabetic drugs that may increase heart failure in high-risk patients. NPY (neuropeptide Y) is coreleased with norepinephrine, causes vasoconstriction via the Y1 receptor, and is degraded by DPP4 to NPY (3–36) in vitro. NPY (3–36) decreases release of norepinephrine via the Y2 receptor. We tested the hypothesis that DPP4 inhibition would potentiate the vasoconstrictor effect of NPY. Eighteen nonsmokers (12 healthy controls and 6 with type 2 diabetes mellitus) participated in 1 of 2 randomized, double-blind, placebo-controlled crossover studies. First, subjects were randomized to order of treatment with sitagliptin 100 mg/d versus placebo for 7 days separated by 4-week washout. On the last day of treatment, NPY was infused by brachial artery and forearm blood flow was measured using plethysmography. Blood samples were collected after each dose. NPY infusions were repeated after 90-minute washout and intra-arterial enalaprilat. Second, 5 healthy subjects were randomized to crossover treatment with sitagliptin 100 mg/d plus valsartan 160 mg/d versus placebo plus valsartan. NPY infusions were performed on the seventh day of treatment. NPY caused dose-dependent vasoconstriction. During enalaprilat, sitagliptin significantly potentiated NPY-induced vasoconstriction in controls and diabetics ( P ⩽0.02 for forearm blood flow in either group). Baseline norepinephrine release was increased during sitagliptin and enalaprilat, but not further by NPY. Sitagliptin increased the ratio of NPY to NPY (3–36). During valsartan, sitagliptin also significantly potentiated NPY-induced vasoconstriction ( P =0.009 for forearm blood flow). Potentiation of endogenous NPY could contribute to cardiovascular effects of DPP4 inhibitors in patients taking an angiotensin-converting enzyme inhibitor or angiotensin receptor blocker. Abstract : Supplemental Digital Content is available in the text.